Intermedial relations in a literary text - Prihodko, Ganna; Prykhodchenko, Oleksandra; Vasylyna, Roman (Cognition, Communication, Discourse, 2024)
This theory aticle attempts to synthesize and modify the views on intermediality as a new field of research. We also aim to illustrate our insights into various verbal and non-verbal media and their correlations by examples from literary texts. Intermediality attracted scholars’ attention at the end of the 20th century. It satisfied the requirement to rearrange the thousand-year-old traditions of the synthesis of arts from the perspective of modern literary, cultural and linguistic thoughts. Intermediality refers to the interaction between literary text and non-verbal sign systems, constituting a multi-code creolized message. The implementation of intermedial relations is carried out through the objectification of different types of art in a literary text at a compositional-structural and figuratively-stylistic level. The blend of codes of various arts within the framework of a literary text becomes possible due to the mark of openness, which allows us to consider each point of the literary text as a single “organism”, capable of self-development. Using the external semiotic environment of the semiosphere and attracting new codes of perception, the literary text repeatedly reconstructs and dynamically develops its intermedial structure interacting with other sign systems. Intermediality includes multisensory experiences and is not only bound to the visible space, as in traditional art fields, but allows an open definition of what art is. Intermedial studies are focused on the interaction of similarities and differences between media and the changes that may occur in communicative material when it is transported from one media type to another. The application of intermedial relationships is carried out through the objectification of several kinds of art in a literary text at a compositionally-structural and figuratively-stylistic point. We claim that focusing on the interaction between works of different types of art, taking into account the multidirectional nature of these relations, and including them in the connections of art and culture forms a new intermedial framework. This framework allows to identify the properties of a literary text as such and the style of a particular author or national literature of a certain period taking into consideration the general rules of literature and art development.